Effect of Exchange Rate Pass-through on Producer and Consumer Prices:Türkiye, Brazil, and South Africa - Ahmet Ekrem Kaya (İktisat Politikası Araştırmaları Dergisi)
The exchange rate is one of the prominent determinants of inflation, among the macroeconomic instability indicators. It is transmitted to domestic prices via cost, expectation, and indexation channels. As such, the exchange rate affects both consumer prices and producer prices. Several countries show trend similarity in terms of weak international reserves, short-term external debt stock, and current account deficit problems that may put pressure on the exchange rate. The aim of the study is to examine whether the affinity of the indicators that will cause the exchange rate to increase creates a similarity regarding exchange rate pass-through. Thus, exchange rate pass-through, which is a strong inflation dynamic, can be evaluated comparatively. Analysis results for 1995Q1:2020Q1 using the Autoregressive Distributed Lag method show that Turkey, Brazil, and South Africa have strong exchange rate pass-through. The increase in the exchange rate causes prices to increase in the long run, with the highest increase in Brazil and the relatively least in Turkey, among the three countries. The results show that countries are similar regarding strong exchange rate pass-through but differ concerning the level of exchange rate pass-through. Granger causality is determined from the exchange rate to the Consumer Price Index in all three countries. Causality from the Consumer Price Index to the exchange rate is only seen in Türkiye and Brazil. While Granger causality from the exchange rate to the Producer Price Index is only valid for Turkey and Brazil, causality from the Producer Price Index to the exchange rate can only be determined for South Africa.